Graph cutting and its application to biological data - Ždímalová Mária (Open Physics, 2019)
In this paper we introduce the concept of segmentation based on mathematical approach using graph theory algorithms using the family of augmenting paths algorithms. We present a new program, an implementation, algorithms and obtained results devoted to segmentation of biomedical data. We implement our program for handling with segmentation, counting a measure of the existence of the minerals in the biomedical data. As a consequence we prove the existence of minerals in the data obtained from the brain of rabbits.